Effectiveness of the combination of marmet technique and oxytocin massage against the breast milk production of mother postpartum - Sagita Darmasari; Eryani Putri; Indah Rahmadaniah (JURNAL KEDOKTERAN DAN KESEHATAN, 2019)
According to UNICEF improper Behaviourand less of knowledge contributed to the death of  a child, one of them, namely the mothers do not realize the importance of breast feeding. According to Basic Medical Research percentage of breastfeeding pattern <1 hourin 2010 i.e. 29,3% and increased to 34,5% in 2013. The breastfeeding patterns 1-6 the first hour of the in 2010 as many as 40,7% and decreased to 35,2% in 2013. A few methods to help improve the ASI production such as oxytocin massage methods, marmet technique, warm compresses, massase rolling (back), breast care, and methods of SEMOS (Stimulation of Endorphin Massage, Oxytocin and Suggestive). This research aimed to know the effectiveness combination of the mermet technique and oxytocin message against the breast milk production of  mothers postpartum. This research used quasi alphabets experiment withpost testmenthods only with control group design. The results of using independent T-bivariat test obtained p value 0,007 < ? (0,05) which means therewas a significant influence between breast milk production of mother postpartum group intervene the breastmilk production of mother postpartum with control group with an average of breast milk production of 30 respondents were  divided into two groups that was 15 respondents of the intervention group obtained 1,113cc whereas 15 respondents of control group obtained 0,547cc. The combination of the marmet technique and oxytocin massage and was effective to stimulatehormone prolactin spending that would stimulate the cells of the alveoli and contain myoepithelial for breast milk  Production of mothers postpartum process on the first days after birth..